SMART CONTRACTS FOR DECENTRALIZED IDENTITY: EMPOWERING CITIZENS IN GOVERNMENTAL ECOSYSTEMS - Oktian, Yustus Eko; Hilton, Kei Patrick; Handoyo, Jeffri Lieca (Universitas Lancang Kuning, 2025)
The rapid digitization of governmental services has underscored the urgent need for secure and efficient identity management systems, particularly within e-government ecosystems. Traditional centralized systems suffer from vulnerabilities such as data breaches, lack of user autonomy, and dependence on single points of control. This study proposes a decentralized identity system leveraging blockchain technology to address these limitations. Our framework employs factory-based smart contracts, hierarchical authority structures, and robust validation mechanisms to ensure trust, security, and interoperability among government entities. Through detailed implementation and testing, the system demonstrates its capability to enhance privacy, streamline identity verification, and maintain data integrity. This paper provides a practical, scalable solution for modern e-governance, setting a foundation for future research and adoption.